DSN1 drives breast cancer progression via cell cycle regulation: diagnostic and therapeutic implications - Liu, Dongyang; Luis, Manuel A.; Sherilyn H. G., Djojomoenawi; Zhu, Xiaoxuan; Zhang, Xiuqin; Fang, Yuan; Lin, Xiaoyan; Tang, Shasha; Cai, Fengfeng (Frontiers in Oncology, 2026)
AimBreast cancer is the most prevalent form of cancer among females and carries a substantial societal impact. DSN1, a component of the MIS12 complex, plays a critical role in centromere assembly, distribution, and stability. While DSN1’s role in tumors has been investigated, its specific function in breast cancer remains unclear.MethodsFirst, we utilized bioinformatics techniques to explore DSN1 expression in breast cancer and conducted functional enrichment and correlation analyses. Subsequently, we assessed the clinical relevance of DSN1 through immunohistochemistry. Furthermore, we examined how DSN1 affects the growth of breast cancer cells by conducting CCK8 and colony formation tests. Cell cycle and apoptosis changes were assessed using flow cytometry. Moreover, we examined key genes related to cell cycle and apoptosis to further elucidate the underlying mechanisms. Finally, we screened potential drugs targeting DSN1 by drug sensitivity and molecular docking analyses.ResultsBioinformatics analysis revealed that DSN1 is highly expressed in breast cancer, making it a potential diagnostic marker. Functional enrichment analysis indicated that the DSN1- overexpressed group was enriched in cell proliferation-related pathways. Cellular experiments confirmed that DSN1 promotes breast cancer proliferation by affecting cell cycle pathways, involving key molecules such as CCNB1, CCND1, CKD1, CDK4, and CDK6. Drug sensitivity analysis showed that the DSN1 high expression group was resistant to drugs such as Epirubicin, Cyclophosphamide, Ribociclib, and Palbociclib, but relatively sensitive to tamoxifen and lapatinib.ConclusionsDSN1 contributes to breast cancer progression by modulating cell cycle pathways, making it a potential diagnostic and therapeutic target with clinical applicability.